“ANÁLISIS DE LA METODOLOGÍA APLICADA PARA EL DESARROLLO DE LAS DESTREZAS LISTENING-SPEAKING EN LOS ESTUDIANTES DEL QUINTO SEMESTRE DE LA ESCUELA DE IDIOMAS, FACULTAD DE CIENCIAS DE LA EDUCACIÓN, HUMANAS Y TECNOLOGÍAS DE LA UNACH PERIODO 2013-2014” - Montesdeoca Flores, Delia Corina (2014)
The methods of teaching foreign languages have evolved throughout history, listening and speaking skills are considered as a solid support in the methodology of the English language , because through these students are able to interact within the classroom in order to achieve significant acquisition of knowledge , also aims to help them who have difficulty listening and speaking skills . It is also important to teachers know the concepts underlying teaching and learning a language . To determine the field research surveys and observation sheets applied ; after conducting an analysis using statistical tables themselves were represented in cakes to reach the hypothesis testing , together with conclusions and recommendations determining the students are at an average level , by the lack of skills and skills in this subject , by the little incentive the student has for learning English